2012
DOI: 10.1017/s1368980012004971
|View full text |Cite
|
Sign up to set email alerts
|

Serum micronutrient status and nutrient intake of elderly Yoruba people in a slum of Ibadan, Nigeria

Abstract: Objective: The present study was conceived in response to a perceived lack of data about the nutritional status of free-living elderly Yoruba people living in a poor urban area in south-western Nigeria. The major focus was to assess the micronutrient status of elderly Yoruba people living in a slum of Ibadan. Design: A cross-sectional descriptive study was designed to collect data on dietary intake and micronutrient status. Setting: By means of a structured questionnaire and the estimated food record method, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Concerning of dietary habits' domain found that the majority of the study sample is revealed significant response. The results consistent when study the health protective behaviors, and they found that the majority of the study subjects are taking their meals sufficiently and efficiently (12,13) . This provides evidence that these elderly clients behaviors committed proper diet that help them to maintain the management of their stable angina and adhere to it .…”
Section: Discussionmentioning
confidence: 52%
“…Concerning of dietary habits' domain found that the majority of the study sample is revealed significant response. The results consistent when study the health protective behaviors, and they found that the majority of the study subjects are taking their meals sufficiently and efficiently (12,13) . This provides evidence that these elderly clients behaviors committed proper diet that help them to maintain the management of their stable angina and adhere to it .…”
Section: Discussionmentioning
confidence: 52%
“…Both cohorts had relatively higher levels of homocysteine than those reported for the general US population but levels of folate and vitamin B12, although significantly different between cohorts, all fell within the US norms (Deeg et al ., 2008). The diet of the elderly Yoruba has been reported to be low in B vitamins including folate (Olayiwola et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Besides these two retrospective methods, weighed records were also utilized, but in a much smaller number; only four studies. Haileslassie et al (2013) and Gibson et al (2008) used only a single day as a measuring unit while Olayiwola et al (2012) and Abebe et al (2008) applied food records for three and two nonconsecutive days, respectively. More detailed information about these studies is compiled in Table 4.…”
Section: Dietary Assessment Methodsmentioning
confidence: 99%
“…In Western African countries the most used nutritional programs were ESHA Food Processor Ò (Food Processor Diet Analysis and Fitness Software) (Wiig and Smith, 2007;Huybregts et al, 2009;Addo et al, 2011;Pereko et al, 2012) and C-SIDE (Sodjinou et al, 2008;Sodjinou et al, 2009;Becquey and Martin-Prevel, 2010;Zeba et al, 2014). Several authors used other softwares, such as NutriData, developed in California (Olayiwola et al, 2012), Nutrition Data System for Research (NDSR), developed by University of Minnesota (Luke et al, 2011) and Nutrifiq, based on the Canadian Nutrient File (Alaof e et al, 2009). A very comprehensive software system, named VBS Food Calculation System, was chosen for the Women's Dietary Diversity Project (in Burkina Faso and Mali) (Becquey et al, 2009;Kennedy et al, 2009).…”
Section: Methods For the Analysis Of Food Intake Datamentioning
confidence: 99%
See 1 more Smart Citation